Factors Affecting Financial Literacy of MSMEs: A Conceptual Framework - Nurul Nur Aeni; Maulida Nurul Innayah (Proceedings Series on Social Sciences & Humanities, 2022)
The purpose of this article is to figure out the elements that impact the monetary proficiency of MSMEs. The strategy utilized recorded as a hard copy this article is by utilizing the writing concentrate on technique. Writing concentrate on examinations different reference books and articles from the aftereffects of past exploration in light of public and global diaries that are pertinent to the subject of conversation, to be specific the elements that influence the monetary proficiency of MSMEs in Banyumas. In light of the consequences of past examinations, the variables that influence the monetary proficiency of SMEs are: age, education, gender, length of work, and income. The degree of monetary education keeps on expanding alongside the familiarity with the significance of monetary proficiency. Notwithstanding, the degree of monetary proficiency in Indonesia actually should be improved, for MSMEs, particularly in the Banyumas region